Contribution of the polymorphism rs1800469 of transforming growth factor β in the development of myocardial infarction: meta-analysis of 5460 cases and 8413 controls (MOOSE-compliant article) - Du, Ling; Gong, Tao; Yao, Minghui; Dai, Henghua; Ren, Hong Gang; Wang, Haitao (Medicine (Baltimore), 2019)
Studies investigating the association between transforming growth factor (TGF-β-509C/T, rs1800469) promoter polymorphism and myocardial infarction (MI) risk reported inconsistent results. The aim of our study was to assess the association between the 509C/T polymorphism of the TGF-β gene (rs1800469) and MI risk.A total of 5460 cases and 8413 controls in 7 case-control studies were incorporated in our current meta-analysis. The original studies were selected through searching the databases of the PubMed and EMBASE. The odds ratio (OR) and 95% confidence interval (95% CI) of TGF-β 509C/T (rs1800469) for MI risk were applied to estimate the strength of the association.Our results showed that T allele carriers had a 13% increased risk of MI, when compared with the C allele carriers (OR = 1.13, 95% CI: 1.00-1.27). In the subset analysis by the type of MI, significantly elevated risk of MI was associated with the homozygote TT and heterozygote C/T in no-AMI subjects, when compared with the CC homozygote carriers (OR = 1.12, 95% CI:1.02-1.23).Our meta-analysis shows that the polymorphism with homozygote TT and heterozygote C/T of TGF-β 509C/T (rs1800469) is significantly associated with the increased risk of MI.